Empowering Adolescents and Young People Through Socializing the Dangers of Online Game Addiction in Ranjeng Village, Losarang District - Indramayu - Ismatul Lu'lu; Ibnudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The aim of this community service (PkM) is to find out about empowering teenagers and youth through socializing the dangers of online game addiction in Ranjeng Village, Losarang District - Indramayu. The approach used in the education program on the dangers of online game addiction is to use the classical guidance method with lectures and question and answer discussions. The result of this community service (PkM) is that consistent and continuous efforts are required from parents in carrying out the task of caring for, nurturing and educating their children physically and mentally until a child matures and is able to stand alone as a responsible human being. answer.